Poesia, realisme i «realisme històric» - Balaguer, Enric (Caplletra. Revista Internacional de Filologia, 2000)
Resum: This essay revises the contribution that Catalan poetry of the 1950s and 60s made to the aesthetic trend of realism, or rather neo-realism. It is also concemed with its contribution as a movement, focusing on the most important poets, among them, Vicent Andrés Estellés, Miquel Martí i Pol, Josep María Llompart i Gabriel. Paraules clau: poesia; realisme; realisme històric; neo-realisme; Vicent Andrés Estellés; Miquel Martí i Pol; Josep Maria Llompart i Gabriel